Design a Programmable Sequence Controller Utilizing I2C BUS - Raafat. S. Habeeb (Journal of Madenat Alelem University College, 2011)
New technology makes possible to manufacturing a better type of programmable micro-system. Recently, Chip with the CPU, RAM, ROM, TIMERS, UARTS, and PORTS is available. These types of chip are called microcontroller. Microcontroller/Microprocessor is a programmable device, which executes a loaded program sequentially from top to down (end of program). This type of controller suffer from non-retain last state problem. At any time the electrical power is turned off, the Microcontroller/Microprocessor will start from initial state after power is turned on, losing all intermediate states. If this problem is solved, it might be the Microcontroller/Microprocessor used as programmable sequence controller efficiently. This paper provides a design of sequence controller based on a microcontroller utilizing Serial Electrical Erasable Read Only Memory (SEEPROM) to save the status of process event sequentially. Serial EEPROM is interfaced to the microcontroller via I2C serial BUS, which is a two wire bus using special protocol to transfer data between microcontroller and serial memory. The sequencer is provided with MINI keypad to select the pre-defined time interval through scrolling UP and DOWN the interval values which is monitor in LCD display. This design had been manufactured and tested by controlling the medical syringe process for long time without serious problem.